Pendekatan One Villace One Product (OVOP) Untuk Meningkatkan Daya Saing Unggulan Industri Kecil Menengah di Desa Lampisang Kabupaten Aceh Besar - Pristiwa, Nara; Agustina, Maya; Yusuf, Yuslaidar; Amelia Sativa, Natasya (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2024)
As technology advances, it encourages small and medium-sized enterprises (SMEs) to utilize technology in marketing their products to boost the regional or national economy. The Lampisang area has SMEs that run similar businesses but compete despite being neighbors, without promoting the name of the region. The One Village One Product (OVOP) program is expected to enhance local potential in a specific area/region, thereby addressing poverty and unemployment. The main objective of this community service is to provide an understanding of the products produced by SMEs in Lampisang village, Aceh Besar, to promote their village as One Village One Product. This aims to improve the competitive advantage of small and medium industries in Lampisang village, Aceh Besar, through this counseling. It is expected that this community service will give SMEs new ideas and insights on how to increase the competitive advantage of small and medium industries in the village. This service is conducted through counseling with the One Village One Product (OVOP) approach to enhance the competitive advantage of small and medium industries in Lampisang village, Aceh Besar. Data collection techniques involve field surveys and information from village officials, followed by interviews with SMEs based on the gathered data. The counseling is conducted face-to-face, with a question-and-answer session providing solutions to any problems encountered so far. The findings during the counseling show that many SMEs have never heard of OVOP. Thus, in the future, SMEs have suggested that community service continues with different themes to help them become more confident and motivated in running their businesses.